Image processing and analysis for intelligent diagnostic colonoscopic instrusmentation system - Marta Patricia Tjoa (2008)
Colorectal cancer is a common cancer prevalent in Singapore and other countries. The early detection of colorectal cancer in patients by frequent check-ups is important to reduce mortality rate. Minimally invasive colonoscopic procedures are increasingly employed for screening, diagnostic and surgical purposes as well as initiation appropriate follow-up actions.